1989
DOI: 10.1111/j.1751-1097.1989.tb04164.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Yields for Laser Photocyclization of Bilirubin in the Presence of Human Serum Albumin. Dependence of Quantum Yield on Excitation Wavelength

Abstract: The quantum yield for laser photocyclization of bilirubin to lumirubin in the presence of human serum albumin (phi LR) was measured at five monochromatic excitation wavelengths in the range 450-530 nm. Solutions used were optically thin throughout the wavelength range and precautions were taken to exclude contributions from photocyclization of bilirubin XIII alpha impurities. The values obtained (7.2-18 x 10(-4] were lower than those previously reported and showed the following wavelength dependence: 457.9 les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 55 publications
5
77
0
2
Order By: Relevance
“…In addition, the calculations allowed us to predict that a narrow wavelength-band emitting light source, such as light-emitting diodes (LEDs), at 476 nm would be the most efficient for phototherapy and would also minimize heating of the neonate by absorbed light. Previous observations (5,15,16) that the optimal wavelength range for phototherapy is at longer wavelengths than the maximum of the bilirubin absorption spectrum (460 nm) are strongly supported by these calculations. …”
supporting
confidence: 70%
See 3 more Smart Citations
“…In addition, the calculations allowed us to predict that a narrow wavelength-band emitting light source, such as light-emitting diodes (LEDs), at 476 nm would be the most efficient for phototherapy and would also minimize heating of the neonate by absorbed light. Previous observations (5,15,16) that the optimal wavelength range for phototherapy is at longer wavelengths than the maximum of the bilirubin absorption spectrum (460 nm) are strongly supported by these calculations. …”
supporting
confidence: 70%
“…The two main transformations are configurational isomerization (to Z,E-bilirubin) and structural isomerization (to lumirubin). It is suggested that the rapidly excreted lumirubin is a key product regards phototherapy (16,26). Both the formation of Z,E-bilirubin and lumirubin exhibit wavelengthdependent yields.…”
Section: Action Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…1 At these wavelengths, light penetrates the skin well and is absorbed strongly by bilirubin. 1,2 Thus, special blue fluorescent (BB) tubes that have their output primarily in the blue spectrum (430 to 490 nm) are recommended by the American Academy of Pediatrics (AAP) as the most effective light source for lowering the serum bilirubin. 3 Prototype light-emitting diode (LED) lights have been developed and tested in clinical and laboratory studies, [4][5][6] and a commercially available LED device is being used, currently, in nurseries in the United States.…”
Section: Introductionmentioning
confidence: 99%